The Long-Term Impact of International Migration on Economic Decision-Making: Evidence from a Migration Lottery and Lab-in-the-Field Experiments - John Gibson; David McKenzie; Halahingano Rohorua; Steven Stillman (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
We study how migration from a poor to a rich country affects key economic beliefs, preference parameters, and transnational household decision-making efficiency. Our setting is the migration of Tongans to New Zealand through a migration lottery program. In a ten-year follow-up survey of individuals applying for this program we elicit risk and time preferences and pro-market beliefs. We also link migrants and potential migrants to a partner household consisting of family members who would stay behind if they moved. We play lab-in-the-field games designed to measure the degree of intra-family trust and the efficiency of intra-family decision-making. Migration provides a large and permanent positive shock to income, a large change in economic institutions, and a reduction in interactions with partner household members. Despite these changes, we find no significant impacts of migration on risk and time preferences, pro-market beliefs, or in the decision-making efficiency of transnational households. This stability in the face of such a large and life-changing event lends credence to economic models of migration that treat these determinants of decision-making as time-invariant, and contrasts with recent evidence on preference changes after negative shocks.
Keywords: O12; F22; D13; D81; P1; 330; Migration; economic beliefs; preferences; household efficiency; transnational household